Learning and Language: Supporting Group Work So Group Work Supports Learning - Mylett, T.; Gluck, R. (Journal of University Teaching and Learning Practice, 2005)
This paper reports on developments in teaching andlearning for first year employment relations students atthe University of Wollongong based on creatingconditions of learning informed by Vygotsky’s ‘zone ofproximal development’ theory. Essentially, this meantemphasising collaborative learning (group work) in thelecture theatre and in assessment tasks to provideopportunities for students to ‘learn the language’ ofemployment relations. The paper also considerscollaboration between an employment relations disciplinelecturer and an learning development discipline lecturerthat helped identify the objectives for teaching andlearning (the desired attributes of a WollongongGraduate, ethical concerns about how students’ mayaffect one another in group work, and developingknowledge and skills to equip students to be effective inemployment relations practice) within a particular taskenvironment (characterised by an organisationalimperative to ‘do more with less’, and students’ beliefsthat lectures have the purpose of didactic informationdelivery) simultaneously with teaching. This paper offersreaders a case study of the application of a teaching andlearning theory that may stimulate reflection on theirpractice.